Evaluation of the stressed deformed state of paint and varnish coatings of cement concretes depending on the quality of appearance - V.I, Loganina; Yu. P., Skachkov; V. S., Demyanova (International Journal of Engineering and Technology, 2018)
Information on the application of holography for the evaluation of the stress-strain state of paint coatings is given. It is shown, that the concentration of stresses is observed in the places of inclusions, ripples, streaks, shagreen. At these points a disturbance in the interference pattern is observed. It is revealed, that a more stressed state occurs in coatings with a higher roughness. This contributes to the early destruction of the coating during operation. It was found, that there is a proportional relationship between the initial roughness of the coating and the probability of its destruction. The results of studies of the resistance of coatings are presented depending on the quality of the appearance of the surface.Â Â